Modeling Depolarization Delay, Sodium Currents, and Electrical Potentials in Cardiac Transverse Tubules - Vermij, Sarah Helena; Abriel, Hugues; Kucera, Jan Pavel (Frontiers in Physiology, 2019)
T-tubules are invaginations of the lateral membrane of striated muscle cells that provide a large surface for ion channels and signaling proteins, supporting excitation-contraction coupling. T-tubules are often remodeled in heart failure. To better understand the electrical behavior of T-tubules of cardiac cells in health and disease, this study addresses two largely unanswered questions regarding their electrical properties: (1) delay of T-tubular membrane depolarization and (2) effects of T-tubular sodium current on T-tubular potentials. Here, we present an elementary computational model to determine the delay in depolarization of deep T-tubular membrane segments as the narrow T-tubular lumen provides resistance against extracellular current. We compare healthy tubules to tubules with constrictions and diseased tubules from mouse and human, and conclude that constrictions delay T-tubular depolarization, while diseased T-tubules depolarize faster than healthy ones due to tubule widening. Increasing tubule length non-linearly delays depolarization. We moreover model the effect of T-tubular sodium current on intraluminal T-tubular potentials. We observe that extracellular potentials become negative during the sodium current transient (<-40 mV in constricted T-tubules), which feedbacks on sodium channel function (self-attenuation) in a manner resembling ephaptic effects that have been described for intercalated discs where opposing membranes are close together. The intraluminal potential and sodium current self-attenuation depend on sodium current conductance. These results show that (1) changes in passive electrical properties of remodeled T-tubules cannot explain excitation-contraction coupling defects in diseased cells; and (2) sodium current may modulate intraluminal potentials. Such extracellular potentials might also affect excitation-contraction coupling and macroscopic conduction.